2017
DOI: 10.4041/kjod.2017.47.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomography for the assessment of root–crown ratios of the maxillary and mandibular incisors in a Korean population

Abstract: ObjectiveThis retrospective, cross-sectional study aimed to establish reference data for normal crown and root lengths and the root–crown ratios (R/C ratios) for the mature maxillary and mandibular incisors in a Korean population by using cone-beam computed tomography (CBCT).MethodsWe included 672 Korean patients (141 men and 531 women; mean age, 27.2 ± 7.7 years) who underwent CBCT examinations during various dental treatments. Crown and root lengths and the R/C ratios of the maxillary and mandibular incisors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Host-related variables included age (,20 years, !20 years), 10 sagittal skeletal pattern (Class I, ANB 0À48; Class II, .48; Class III, ,08), 11 vertical skeletal pattern (high, SN-MP .378; normal, SN-MP 27-378; low, SN-MP ,278), 12 overjet (normal, 0-4 mm; excessive overjet .4 mm; crossbite ,0 mm), and overbite (normal, 0-4 mm; deep bite .4 mm; open bite ,0 mm). 13 Miniscrew-related variables included surface treatment type (machined vs acid-etched), insertion site (maxilla vs mandible), and miniscrew purpose (en masse retraction anchorage, retraction; total arch distal movement, distalization; maxillary molar intrusion, intrusion). The model-building strategy involved the inclusion of any variable for which the bivariate test yielded a P value of ,.05.…”
Section: Discussionmentioning
confidence: 99%
“…Host-related variables included age (,20 years, !20 years), 10 sagittal skeletal pattern (Class I, ANB 0À48; Class II, .48; Class III, ,08), 11 vertical skeletal pattern (high, SN-MP .378; normal, SN-MP 27-378; low, SN-MP ,278), 12 overjet (normal, 0-4 mm; excessive overjet .4 mm; crossbite ,0 mm), and overbite (normal, 0-4 mm; deep bite .4 mm; open bite ,0 mm). 13 Miniscrew-related variables included surface treatment type (machined vs acid-etched), insertion site (maxilla vs mandible), and miniscrew purpose (en masse retraction anchorage, retraction; total arch distal movement, distalization; maxillary molar intrusion, intrusion). The model-building strategy involved the inclusion of any variable for which the bivariate test yielded a P value of ,.05.…”
Section: Discussionmentioning
confidence: 99%
“…Another method is with cone beam computed tomography (CBCT) that Choi et al used in samples from Korean population. The tooth length on that study is maxillary central incisor 22.8±1.15 mm and maxillary lateral incisor 21.6±1.0 mm [7]. Research by Harris et al showed the tooth length of central incisor was 26.26±2.49 mm (males) and 25.21±2.14 mm (females), and lateral incisor was 25.15±2.42 mm (males) and 23.78±1.95 mm (females).…”
Section: Tlmentioning
confidence: 69%
“…Radiographic measurements of dental hard tissues are typically evaluated from panoramic, periapical, or Cone Beam Computed Tomography (CBCT) images . Most studies of the R/C ratios use panoramic radiographs, which are relatively inexpensive, accessible, and a part of most new patient exams .…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic measurements of dental hard tissues are typically evaluated from panoramic, periapical, or Cone Beam Computed Tomography (CBCT) images. 13,17 Most studies of the R/C ratios use panoramic radiographs, which are relatively inexpensive, accessible, and a part of most new patient exams. [13][14][15]18 Although panoramic radiographs may have some limitations in terms of the accuracy of measurements compared with CBCT, they provide adequate information and are more practical for the assessment of changes in large number of teeth without additional exposure to radiation 18 .…”
Section: Discussionmentioning
confidence: 99%